Proceedings of the 17th International Conference on Human-Computer Interaction With Mobile Devices and Services 2015
DOI: 10.1145/2785830.2785833
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mobile Devices as Personal Public Displays

Abstract: fixed locations [28] as opposed to smartphones which are used with more frequency and across more contexts [15]. Motivated by the fact that laptops are mobile but seemingly unsuitable beyond a few set locations, we sought to address this gap between the perceived usefulness of laptops for productivity and the possibility for its relevance across an increasing number of social contexts.To explore the potential ways that laptops might be more socially relevant to people across different environments, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…However, they did find that scanning the environment to find others was a core use function. Recently, Kleinman et al (2015) investigated how an additional outwardly facing display attached to a notebook computer, called Billboard, was used in different settings (e.g., conference, office and university). Billboard enabled users to post texts and images to the second display.…”
Section: Digital Presentation Of Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did find that scanning the environment to find others was a core use function. Recently, Kleinman et al (2015) investigated how an additional outwardly facing display attached to a notebook computer, called Billboard, was used in different settings (e.g., conference, office and university). Billboard enabled users to post texts and images to the second display.…”
Section: Digital Presentation Of Selfmentioning
confidence: 99%
“…Billboard enabled users to post texts and images to the second display. Kleinman et al (2015) found that, in addition to functional purposes, such as leaving a note to others, Billboard was used to make connections to nearby people based on the media they were willing to share. However, they did not analyse if, and in what way, media was used during face-to-face interactions.…”
Section: Digital Presentation Of Selfmentioning
confidence: 99%
“…As the participant numbers differ between groups, the data were normalised to be representative. Our participants consisted of 20 males and eight females (M = 27, range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Most users were strangers (91%), with 7% being friends and 2% classified as 'known people' (familiar strangers).…”
Section: Participantsmentioning
confidence: 99%
“…Previous work focused on lab experiments [6] or a narrow context [2,3]. Thus, a first step is gaining a broader understanding of context as a factor for augmented self-presentation.…”
Section: Research Conducted So Farmentioning
confidence: 99%